REPRESENTASI PEREMPUAN DALAM IKLAN KOMERSIAL : ANALISIS FEMINIS PADA MEDIA TELEVISI - Kholillul Rohman (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This research aims to identify and analyze the representation of women in commercial advertisements from a feminist perspective. The method used is library research with a qualitative approach. Data was collected through document analysis of Indonesian television advertisements and analyzed using a feminist framework from previous literature. The results showed that the representation of women in television advertisements is still dominated by gender stereotypes and traditional roles. The dynamics of women's representation in commercial advertisements in Indonesian television media are marked by the persistent dominance of gender stereotypes, unrealistic idealization of body and beauty, inequality in the representation of diversity, and subordinate roles in advertising narratives. The findings also reveal significant changes in line with increasing gender awareness and the influence of the feminist movement marked by recent advertisements that feature women in non-traditional roles that are more independent and empowered, and emphasize the values of empowerment and gender equality. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis representasi perempuan dalam iklan komersial dari perspektif feminis. Metode yang digunakan adalah library research dengan pendekatan kualitatif. Data dikumpulkan melalui analisis dokumen iklan televisi Indonesia dan dianalisis menggunakan kerangka feminis dari literatur terdahulu. Hasil penelitian menunjukkan bahwa representasi perempuan dalam iklan televisi masih didominasi oleh stereotip gender dan peran tradisional. Dinamika representasi perempuan dalam iklan komersial di media televisi Indonesia ditandai dengan dominasi stereotip gender yang persisten, idealisasi tubuh dan kecantikan yang tidak realistis, ketimpangan dalam representasi diversitas, dan peran subordinat dalam narasi iklan. Temuan juga mengungkap adanya perubahan signifikan seiring meningkatnya kesadaran gender dan pengaruh gerakan feminis yang ditandai dengan iklan-iklan terbaru yang menampilkan perempuan dalam peran non-tradisional yang lebih mandiri dan berdaya, serta menekankan nilai-nilai pemberdayaan dan kesetaraan gender.